2023
DOI: 10.1021/acsaom.3c00240
|View full text |Cite
|
Sign up to set email alerts
|

Generating Angular-Varying Time Delays of THz Pulses via Direct Space-to-Time Mapping of Metasurface Structures

Elazar Elias,
Symeon Sideris,
Cormac McDonnell
et al.

Abstract: We experimentally demonstrate the generation of double terahertz (THz) pulses with tailored angular-dependent time delays from a nonlinear metasurface excited by a near-infrared femtosecond pulse. The tailored temporal properties of the generated pulses emerge from a direct mapping of the nonlinear spatial response of the metasurface to the emitted THz temporal profile. We utilize the Pancharatnam-Berry phase to implement symmetric and antisymmetric metasurface configurations and show that the emitted patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In ultrafast optical information processing, some previous works have demonstrated that ultrafast time-varying effects induced by two time-delayed femtosecond pulses can be used in the fields of optical switching, time-varying holographic imaging, and beam modulation. Here the time-varying OAM of femtosecond SPP vortex can also be used in ultrafast switching of optical information [47,48], especially with the nonlinear materials or with OAM-multiplex structures.…”
Section: Discussionmentioning
confidence: 99%
“…In ultrafast optical information processing, some previous works have demonstrated that ultrafast time-varying effects induced by two time-delayed femtosecond pulses can be used in the fields of optical switching, time-varying holographic imaging, and beam modulation. Here the time-varying OAM of femtosecond SPP vortex can also be used in ultrafast switching of optical information [47,48], especially with the nonlinear materials or with OAM-multiplex structures.…”
Section: Discussionmentioning
confidence: 99%